RIESGO DE CONTRAER ENFERMEDADES PARASITARIAS EN LOS PARQUES PÚBLICOS DE LIMA Y CALLAO. - Chávez V., Amanda (2002)
The objective of this paper was to determine the contamination with Toxocara sp. in public parks ofMetropolitan Lima and Callao. Turf samples were collected from 558 out ofthe 1,964 parks existing in Lima and Callao (108, 98, 151and123 from the northern, southern, eastern and western part ofLima and 78 from Callao) during December 1998 and August 199 using the double "W" method. Samples were processed by the flotation method using ClNa saturated solution. A sample was considered positive when presented at least one egg of Toxocara sp. The eggs were incubated and orally inoculated to mice and quails to verify the viability of eggs. Parks were grouped according to the level of conservation as good (well covered with grass), moderate (around 50% covered with grass) and poor conserved (without grass); and according to the social economic level as high, middle-high, middle, middle-low and low. The prevalence rate was 34 ± 9% (mean ± confidence interval), 30±9,41±8, 63 ± 9 and 37±11 % forparks innorthern, southern, · eastern and western part ofLima and Callao, respectively. Contamination level was 73, 49 and 16% in parks with good, moderate and poor level of conservation, whereas according to the social economic level was 73, 62, 47, 29 and 30% in parks with high, middle-high, middle, middle-low and low social economic levels, respectively. Abundant green material and high humidity in good conserved parks would favour conservation of Toxocara sp. eggs. On the other hand, the absence of Toxocara sp. eggs in poorly conserved parks would be dueto direct solar radiation on the eggs. Finally, inoculated mice and quails developed migrant larva, which is indicative of the infective capacity of the eggs.